Hydrogen‐rich water and caffeine for alertness and brain metabolism in sleep‐deprived habitual coffee drinkers. Issue 9 (19th July 2021) - Todorovic, Nikola; Zanini, Dragana; Stajer, Valdemar; Korovljev, Darinka; Ostojic, Jelena; Ostojic, Sergej M.
Abstract: The main aim of this randomized‐controlled cross‐over interventional trial was to assess the acute effects of taking a single dose of hydrogen‐rich water (HRW), and compare it with caffeine, HRW plus caffeine, and control water, for alertness, brain metabolism, brain and oxygen saturation, and self‐reported adverse events in healthy men and women who were habitual coffee drinkers and were sleep‐deprived for 24 hr. Sixteen apparently healthy young adults (8 men and 8 women; age 24.0 ± 3.5 years) were allocated in a cross‐over design to receive a single‐dose drink of HRW (8 ppm), caffeine (50 mg), HRW plus caffeine, or control drink (tap water) in the morning after 24‐hr sleep deprivation and 12‐hr fasting. The primary and secondary outcomes were assessed at baseline (pre‐intervention) and 15‐min follow‐up. Significantly less time was needed to complete trail‐making test after both HRW and HRW plus caffeine compared with the control drink ( p  < .05). The number of errors in the symbol digit modalities test was significantly lower after drinking HRW or caffeine than control drink ( p  < .05). Both HRW and caffeine significantly increased the choline‐to‐creatine ratio in several brain regions (frontal white and gray matter), while HRW and the combination intervention also affected brain metabolism in the paracentral brain. No participants reported any side effects from any intervention. The attention enhancement driven by HRW appears along with changes in brain metabolism. Being generally recognized as a safe intervention, hydrogen could be thus recommended as a novel intervention that upholds attention in stressed conditions, with its metabolic footprint likely different from caffeine. Abstract : Drinking a single dose of hydrogen‐rich water (HRW) improves alertness in sleep‐deprived young men and women. The attention enhancement driven by HRW appears to go with notable changes in brain metabolism, illustrated by higher choline‐to‐creatine ratio levels in the frontal and paracentral brain. Being a harmless intervention, HRW could be thus recommended as a novel food intervention that upholds attention in stressed conditions, with its metabolic footprint likely different from caffeine.